CODING DATA FLOWS METHOD FOR VIRTUAL PROFILED EQUIPMENT IN INTERDISCIPLINARY ENVIRONMENT OF LABORATORY RESEARCHING (Computer systems and information technologies, 2022)
In the present research an improved the technique of coding the specification from widespread software complexes for modeling and designing the subject area is proposed, which is optimized with regard to the specialization of data flows of the built scheme of learning experiment with operational access to information resources and computerized means for appraise demonstrated competencies. Stipulated hierarchy of target categories for simulation model of production stages distinguishes of structured rubrics sets, meaningful records of which represent properties and events in visualization the regular objects, guaranteeing stability of experimental scheme due to unified procedures of subject area processing and absence the arhythmization in algorithm of file format serialization. Thus, related instances of complementary objects of ramified technological map or commenting on graphic pattern the generalized simulation model of experimental scheme provide the completion accompanying hypertags of projected specification, which assure the integration of created media platform into academic information space. The adequacy of modeled data structure is confirmed by saving of user settings by API and the correctness of subject area file processing in file system according to accepted signature.
Keywords: virtual laboratory, learning experiment scheme, subject area, data flows, specification, signature, academic information space.